Perceived Social Support as a Predictor of Teacher Candidates' Smartphone Cyberloafing - Karabatak, Songül; Alanoğlu, Müslim (BİLGE AKADEMİK YAYINCILIK EĞİTİM BİLİŞİM VE DANIŞMANLIK HİZMETLERİ, 2021)
This study investigated whether teacher candidates' perceived social support (PSS) predicts smartphone use during lectures. To achieve the aim of the study, a relational survey model was used. The study sample composed of students studying at the College of Education in Elazığ Province, Turkey, during the 2019-2020 academic semester. The correlation analysis was conducted to determine the relationships among the variables, and hierarchical linear regression analysis was used to determine the predictive effects of demographic characteristics (gender and class) and PSS on smartphone cyberloafing. The results of the study revealed a significant, negative, and low relationship between PSS and smartphone cyberloafing. Social support from family negatively predicted smartphone cyberloafing during lectures, while social support from significant others positively predicted it. Finally, the family and significant other subscales significantly predicted interactive, browsing, and entertainment cyberloafing. In contrast, the friends subscale predicted only interactive cyberloafing. The belief that a sense of trust in family and needed family support in times of need could decrease smartphone cyberloafing and lead teacher candidates to focus more on teaching. Educational institutions should develop policies that involve families at every stage of education, and decisions should be made with the support of experts, institutions, or organizations on problematic issues.
Keywords: Other Fields of Education; Alan Eğitimleri